Cotton aphid (Aphis gossypii Glover: Aphididae) influence associated to water hyacinth nutrient (Pontederia crassipes Mart.: Pontederiaceae) in lath house conditions in Great Rift Valley of Ethiopia - Tatek Kassu; Emana Getu; Diriba Muleta (CABI Agriculture and Bioscience)
Abstract The cotton aphid, Aphis gossypii Glover is a polyphagous herbivore known worldwide. The aphid infestation could be considered as a challenge to crops, but an opportunity for alien invasive weed management. Hence, this study was initiated to investigate the potential of cotton aphid on the management of water hyacinth. Aphid-infested water hyacinth plants were used as a stock for rearing the aphid in a lath house at Ethiopian Sugar Corporation, Research and Development Center, Wonji. After rearing, randomly collected 30 aphids were placed onto water hyacinth plants cultivated under three nutrient levels. Aphid population, water hyacinth biomass and percent nitrogen and phosphorus were analyzed. The water hyacinth treated with a high nutrient level had the highest (295.0) mean aphids on apical leaves followed by the middle (178.3) and basal (104.7) leaves. The water hyacinth subjected to medium and no aphid treatment had the highest dry (44.3 g) biomass. However, when treated with a low nutrient level and aphids resulted in the lowest dry (31.9 g) biomass. Nitrogen and phosphorus concentrations were found high in the water hyacinth that received a high nutrient and no aphid treatment. The presence of the aphids reduced the biomass and nutrient concentration of the invasive weed. The findings of the current study revealed that the cotton aphid affected the water hyacinth in the lath house conditions in Ethiopia.